2014
DOI: 10.1021/la501978u
|View full text |Cite
|
Sign up to set email alerts
|

Loading and Protection of Hydrophilic Molecules into Liposome-Templated Polyelectrolyte Nanocapsules

Abstract: Compartmentalized systems produced via the layer-by-layer (LbL) self-assembly method have been produced by alternatively depositing alginate and chitosan layers onto cores of liposomes. The combination of dynamic light scattering (DLS), ζ potential, and transmission electron microscopy (TEM) techniques provides detailed information on the stability, dimensions, charge, and wall thickness of these polyelectrolyte globules. TEM microphotographs demonstrate the presence of nanocapsules with an average diameter of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 43 publications
(77 reference statements)
0
28
0
Order By: Relevance
“…Matrix capsules are typically prone to a different release mechanism that is mostly determined by the composition and internal molecular structure of the matrix [ 22 ]. Some examples include poly( l -glutamic acid)/chitosan microcapsules templated on melamine formaldehyde [ 51 ], chitosan/alginate capsules built up on liposomes [ 52 ], or carrageenan/chitosan capsules deposited onto oil nanoemulsion droplets [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Matrix capsules are typically prone to a different release mechanism that is mostly determined by the composition and internal molecular structure of the matrix [ 22 ]. Some examples include poly( l -glutamic acid)/chitosan microcapsules templated on melamine formaldehyde [ 51 ], chitosan/alginate capsules built up on liposomes [ 52 ], or carrageenan/chitosan capsules deposited onto oil nanoemulsion droplets [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Alginates are abundant in the environment since they are present both as a structural component in marine brown algae, and as capsular polysaccharides in soil bacteria. Alginate is recognized as a versatile biopolymer used in a broad range of applications [1][2][3][4][5]. Alginate is a linear binary copolymer made of blocks of mannuronic acid (M) and guluronic acid (G), covalently linked together in different sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Cuomo and coworkers reported that low or high molecular weight molecules were released with a non-Fickian type of transport from polyelectrolyte capsules made of alginate and chitosan. The release rate decreased, while the molecular weight and the multishell thickness increased [42,43] (Figure 2).…”
Section: Molecular Diffusion Through Polymeric Capsulesmentioning
confidence: 99%
“…Multilayer film PLL c /liposomes/PMAc/PVP/PMA SH [19,82] Alginate/Chitosan Multilayer film ALG/CHI [7,22,42,43] Poly(sodium-styrene sulfonate)/poly(allylamine) hydrochloride Multilayer film PSS/PAH [5] Glucose oxidase/Catalase Multilayer film GOX/CAT [79] Glucose oxidase/polyethylenimine/Catalase Multilayer film GOX/PEI/CAT [80]…”
Section: Membrane Composition Reference Polymer Name Acronymmentioning
confidence: 99%